Research on Safety and Integrated Disaster Prevention System Based on Big Data Technology - Zhongyang Sun; Danhui Fang; Zeshuai Zhou (International Journal of Informatics and Information Systems, 2023)
Safety integrated disaster prevention system, as a guarantee of national safety, especially to reduce the serious consequences of disasters, promote the steady development of the economic and social level, has important practical value for the comprehensive study of safety and disaster prevention system. However, the current application and update of such systems by relevant government agencies and the social level cannot effectively follow the development needs of the society and the industry, and there is an urgent need for effective reform. Based on this, this paper first analyzes the problems existing in the research and construction system of big data technology in the security and integrated disaster prevention system, and then gives the construction strategy of the research system of safety and disaster prevention in view of these problems.